Striking seasonal pattern of primary production in the river-dominated ocean margin of the northern South China Sea (NSCS-RiOMar) revealed by new field and remotely sensed data. (November 2020) - Xie, Yuyuan; Lin, Lizhen; Xiao, Wupeng; Yu, Xiaolong; Lan, Wenlu; Huang, Bangqin
Abstract: Seasonal patterns of phytoplankton biomass and primary production (PP) are important features characterizing a marine ecosystem. The South China Sea (SCS) has been arbitrarily illustrated as an ecosystem with low PP in summer and high PP in winter. However, there is an emerging consensus about a lack of unity of PP seasonality in the SCS even in the northern SCS shelf-sea. Through analysis of the distributions of the remotely sensed colored dissolved organic matter absorption coefficient, a river-dominated ocean margin in the northern SCS (NSCS-RiOMar) with the 50 m isobath as its southeastern boundary has been defined. The difference in PP seasonality between the NSCS-RiOMar and the whole shelf-sea was evaluated by both the measured and the remotely sensed depth-integrated primary production (ΣPP). A diagnostic analysis found that euphotic depth and a function of the half-saturation light intensity accounted for the seasonal variation of ΣPP in the NSCS-RiOMar. Accordingly, the Platt and Sathyendranath (1993) model plus the nearest neighbor method and the semi-analytical estimates of euphotic depth were used to compute the remotely sensed ΣPP. The average ΣPP in the NSCS-RiOMar were 1146.4, 1604.7, 979.5, and 891.3 mg C m −2 d −1 in spring, summer, autumn, and winter, respectively, contrasted with small seasonal variations in the whole shelf-sea. The unimodal ΣPP peak was in June-July in accordance with the peak of Pearl River discharge. This result was striking because previous remote sensing studies all showed the reversed seasonal pattern of ΣPP in both the NSCS-RiOMar and the whole shelf-sea. The annual PP was estimated to be 33.5 ± 2.3 Mt C yr −1 and 56.2 ± 3.2 Mt C yr −1 in the NSCS-RiOMar and the whole shelf-sea, respectively. The nutrients inputted by the China Coastal Current might account for 4–23% of ΣPP in the NSCS-RiOMar between December and February.